Pengaruh Green Marketing dan Corporate Social Responsibility terhadap Brand Image Waterbom Bali - Putra, I Kadek Gilang Suryana (HeadWay Research & Developemnt, 2025)
This study examines the influence of green marketing and corporate social responsibility (CSR) on the brand image of Waterbom Bali during the Covid-19 pandemic. The pandemic significantly affected Bali’s tourism sector, prompting tourism businesses to strengthen environmental initiatives and social responsibility programs to maintain public trust and competitive advantage. Waterbom Bali, as a CHSE-certified theme park and a carbon-neutral tourism company in Bali, implements various green marketing strategies, including water conservation initiatives, waste management, and environmentally responsible operations, alongside CSR activities aimed at supporting local environmental sustainability. A quantitative–descriptive approach was used, supported by a survey of 160 domestic tourists who visited Waterbom Bali during the pandemic. Data were analyzed using multiple linear regression. The results show that green marketing and CSR both have a positive and significant effect on brand image, either partially or simultaneously. Among the two variables, green marketing has the strongest influence. These findings indicate that environmentally responsible practices and social commitment play an essential role in shaping a positive brand image, particularly in times of crisis. The study highlights the importance for tourism businesses to continuously strengthen green marketing initiatives and CSR programs to enhance consumer perceptions and sustain competitiveness.